STUDI POTENSI EKOWISATA MANGROVE DI KUALA LANGSA PROVINSI ACEH (Study of Ecotourism Mangrove Potency At Kuala Langsa, Province of Aceh) - Arief Baizuri Majid; Pindi Patana; Indra Lesmana (AQUACOASTMARINE, 2014)
Mangrove ecosystem at Kuala Langsa has been used as one of the tourist area which offer tourism to get closer to nature. At this area had built shelters in the middle of the mangrove forest. Futhermore, there are rivers used as a fishing area, and mangrove forests which still inhabited by monkeys makes potentially used as a mangrove ecotourism.This study was conducted in June until July 2013 and held at mangrove areas of Kuala Langsa at District of West Langsa, Langsa, Province of Aceh. This research using analysis vegetation of the mangroves, tourism suitability analysis, analysis of ecotourism attraction, analysis of the economic value and SWOT analysis.Kuala Langsa mangrove ecosystem inhabited by 5 species are Rhizophora apiculata, Rhizophora mucronata, Xylocarpus granatum, Brugueira gymnorrhiza, Scyphipora hydrohyllaceae. Greatest density of mangrove species is Rhizophora apiculata. Index of ecological suitability for tourism activities in the mangrove Kuala Langsa included into the category corresponding conditional. This category has the limiting factor which shows that to make this site as the location for ecotourism, protection of mangrove ecosystem in order to balance and prevent biodegradation of mangrove that cause damage is important thing to do.Keywords : Ecotourism, Kuala Langsa, Mangrove, Potency.